2021
DOI: 10.24016/2020.v7.199
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of academic burnout in college students during the COVID-19 pandemic

Abstract: Background: Academic burnout (AB) is an insidious process characterized by the feeling of emotional exhaustion due to the demands of academic life. Despite its impact on people's health, its prevalence has not yet been reported in Peru. The objective was to estimate the prevalence of AB, based on the emotional exhaustion experienced by university students, and the differences according to the student's year of study and sex. Method: Participants were 341 college students (76% women) from several institutions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 53 publications
0
13
0
12
Order By: Relevance
“…Comenzando por los resultados descriptivos, la media y la desviación estándar informaron que los estudiantes cuentan con niveles intermedios de cansancio emocional (M= 23.73, DE = 9.76). Al segmentar los resultados de acuerdo con su puntuación (bajo [10][11][12][13][14][15][16][17][18][19], medio [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] y alto [40-50]), se observó que el mayor porcentaje de los respondientes se encuentra en la categoría de bajo cansancio emocional. La Figura 1 muestra los porcentajes específicos: Figura 1.…”
Section: Resultsunclassified
“…Comenzando por los resultados descriptivos, la media y la desviación estándar informaron que los estudiantes cuentan con niveles intermedios de cansancio emocional (M= 23.73, DE = 9.76). Al segmentar los resultados de acuerdo con su puntuación (bajo [10][11][12][13][14][15][16][17][18][19], medio [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] y alto [40-50]), se observó que el mayor porcentaje de los respondientes se encuentra en la categoría de bajo cansancio emocional. La Figura 1 muestra los porcentajes específicos: Figura 1.…”
Section: Resultsunclassified
“…It would be advisable for future studies to prepare normative data to know the prevalence of the phenomenon (Seperak-Viera et al, 2021), since the academic context is not unfamiliar with different adverse factors that affect both mental health and academic performance, so its follow-up and monitoring are essential. Likewise, it is necessary to address other groups of college students, such as postgraduate students who are a group scarcely studied and present difficulties associated with their academic life (Barattucci et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies conducted before the pandemic show greater recurrence and intensity of ABS in men than in women (Bikar et al, 2018;Zahedbablaan et al, 2014), although in other studies women score higher (Herrmann et al, 2019;Salmela-Aro et al, 2016), especially in EE Worly et al, 2017Worly et al, , 2019. However, changes and living conditions associated with the pandemic, along with the academic pressure experienced, have caused an increase in ABS, and EE reaching higher levels of discomfort (Jiang, 2021;Seperak-Viera et al, 2021). Additionally, women and college students experienced greater stress than men and the elderly (Xiong et al, 2020).…”
Section: Emotional Exhaustion During the Pandemic: Sex Differencesmentioning
confidence: 99%
“…The effect of the pandemic in Peru had psychosocial repercussions in the community of the education sector due to government health provisions to prevent the spread and massive contagion (Seperak et al, 2021), with the cessation of face-to-face activities for virtual ones at all levels, in that sense, there were changes in the academic and social environment of university students impacting their mental health, observing an increase in anxiety and depression (Cao et al, 2020;Araoz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on academic burnout in Peru during the Covid-19 pandemic describe that: students present moderate levels of academic burnout and according to variables such as sex, age group, work situation and year of studies are associated with burnout (Estrada et al, 2021); in addition, a publication on prevalence and severity of academic burnout indicates that students present high levels of burnout and the risk situation is significant, finding that university women are the ones who score higher than men (Seperak et al, 2021); likewise, Alavedra and Cárdenas (2021) found that the prevalence of burnout syndrome varies between 8% and 57%, manifesting a certain degree of anxiety, depression and stress due to the uncertainty caused by the pandemic, affecting the normal development of academic activities (Prada-Chapoñan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%